Finite element analysis of the tensile strength and puncture resistance of woven fabrics / Mohamad Faizul Yahya - Yahya, Mohamad Faizul (Institute of Graduate Studies, UiTM, 2013)
The tensile, ballistic and puncture impact behavior of woven fabric have been subjectof interests for many researchers. The tensile behavior of woven fabric can be analyzed from the experimental and analytical methodologies. While experimentprovides accurate information about woven fabric’s mechanical properties than the analytical approach, it also generates sample wastage. Finite element analysis (FEA) method is used to model uniaxial tensile, impact and puncture response of woven fabrics in two and three dimensional geometrical model shapes. Woven fabrics models sizes are based on either unit cell or meso-scale (large scale) approach. Nevertheless, limited publications address woven fabric models in terms of weave repeat sizes. Finite element analysis has the ability to represent fabric geometrical properties and their symmetries, with weave mesh structures able to be made as close as possible, with minimal assumptions. Other than ballistic impact performance, limited work is done to model tensile performance of aramid based woven fabrics. In addition to that, many publications neglect the weaves structures influences such as float and yarn crimp to tensile and puncture impact behavior. Hence, in the study, an alternative simulation procedure was proposed to develop the understanding and prediction of float and yarn crimp relationship in uniaxial tensile and puncture impact behavior of isotropic weave repeat unit. Woven fabric geometrical models were developed with TexGen and Abaqus CAD pre-processor module. The study was divided into three critical stages. Initially, FEA models were established on plain 1/1, 2/2 twill and 8 ends satin. Woven fabrics were configured as a balanced weave thereby allowing systematic investigation of the effect of uniaxial tensile stress on the weave. Woven fabrics were designed to have equivalent densities 8 yarns cm-1 for all three weaves…